Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pt. Permata Jaya Kargo Kantor Cengkareng Jakarta Barat - Syauqi Nasiratunnisa; Gunawan Baharuddin (JURNAL MANAJEMEN PENDIDIKAN, 2026)
THE INFLUENCE OF WORK DISCIPLINE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT HOTEL JEEP STATION INDONESIA RESORT MEGAMENDUNG BOGOR This study aims to analyze and determine the influence of Work Discipline (X₁) and Work Environment (X₂) on Employee Performance (Y) at PT. Permata Jaya Kargo, Cengkareng Office, West Jakarta. The persistent high level of employee tardiness and suboptimal work environment conditions are the reasons for this research. Employee performance is a crucial aspect in supporting company operational effectiveness, particularly in the shipping and logistics industry, which demands punctuality, productivity, and service quality. The research method used was a quantitative method with an associative approach. The population in this study was all 85 employees of PT. Permata Jaya Kargo, Cengkareng Office, West Jakarta. The sampling technique used was non-probability sampling with a saturated sampling method, so that all members of the population were included in the study sample. Data collection was carried out through questionnaires that had been tested for validity and reliability. Data analysis techniques used included classical assumption tests, multiple linear regression analysis, coefficient of determination (R²) tests, and partial (t-test) and simultaneous (F-test) hypothesis testing. The research results, based on descriptive analysis, indicate that the variables Work Discipline, Work Environment, and Employee Performance are in the good category. The t-test results indicate that Work Discipline has a partial positive and significant effect on Employee Performance, with a calculated t-value of 6.692, greater than the t-table value of 1.989, and a significance value of 0.000 <0.05. Similarly, Work Environment has a positive and significant effect on Employee Performance, with a calculated t-value of 3.545, greater than the t-table value of 1.989, and a significance value of 0.000 <0.05. The F-test results indicate that Work Discipline and Work Environment simultaneously have a positive and significant effect on Employee Performance. The Adjusted R-square value indicates that Work Discipline and Work Environment are able to explain variations in Employee Performance, while the remainder is explained by other variables outside the research model. The conclusion of this study confirms that improving work discipline accompanied by the creation of a comfortable, safe, and conducive work environment can optimally improve employee performance, thereby supporting operational effectiveness and achieving company goals.